Optimisation of over-expression in E. coli and biophysical characterisation of human membrane protein synaptogyrin 1 - Löw, Christian (2013)
Progress in functional and structural studies of integral membrane proteins (IMPs) is lacking behind their soluble counterparts due to the great challenge in producing stable and homogeneous IMPs. Low natural abundance, toxicity when over-expressed and potential lipid requirements of IMPs are only a few reasons for the limited progress. Here, we describe an optimised workflow for the recombinant over-expression of the human tetraspan vesicle protein (TVP) synaptogyrin in Escherichia coli and its biophysical characterisation. TVPs are ubiquitous and abundant components of vesicles. They are believed to be involved in various aspects of the synaptic vesicle cycle, including vesicle biogenesis, exocytosis and endocytotic recycling. Even though TVPs are found in most cell types, high-resolution structural information for this class of membrane proteins is still missing. The optimisation of the N-terminal sequence of the gene together with the usage of the recently developed Lemo21(DE3) strain which allows the balancing of the translation with the membrane insertion rate led to a 50-fold increased expression rate compared to the classical BL21(DE3) strain. The protein was soluble and stable in a variety of mild detergents and multiple biophysical methods confirmed the folded state of the protein. Crosslinking experiments suggest an oligomeric architecture of at least four subunits. The protein stability is significantly improved in the presence of cholesteryl hemisuccinate as judged by differential light scattering. The approach described here can easily be adapted to other eukaryotic IMPs.